The Effect Of Pregnancy Massage On The Movement Of The Fetus In The Womb In The Second And Third Trimesters Of Pregnancy At TPMB Novi Salim Rajeg In 2022 - Irliana Anggraini; Nur Sitiyaroh (CV. Inara, 2023)
Background : The body of a pregnant woman experiences many changes that can be stressful and painful. Pregnant women may experience discomfort due to skin changes, back discomfort, cramps, fatigue, swelling in the legs, varicose veins and nausea. Purpose of Writing: The Effect of Pregnancy Massage on the Movement of the Fetus in the Womb in the Second and III Trimesters of Pregnancy at TPMB Novi Salim Rajeg in 2022. Research Method : Quantitative research using experimental design. the overall sample in this study. Those who examined at TPMB Novi Salim Rajeg who met the research criteria included inclusion criteria, namely being willing to be a respondent, pregnant women in the second or third trimester, while the exclusion criteria were pregnant women experiencing skin allergies, pregnant women having complications in pregnancy. As for the sample in this study, there were 20 people, namely 10 participants getting pregnancy massage in the intervention group (10 in the control group) (pregnant women were not given pregnancy massage. Results: The findings of the paired sample t test in the intervention group showed the difference between before and after pregnancy massage on fetal movements in the womb during the second and third trimesters of pregnancy, with a value of p = 0.000 ( 0.05), indicating no difference before and after pregnancy. However, the intervention group was more active for 24 hours compared to the control group with a P value of 0.000 which indicated that pregnancy massage had an impact on fetal movements in the womb during the second and third trimesters of pregnancy at Novi Salim Rajeg TPMB 2022. Conclusions and Suggestions: It is hoped that the results of this research can be applied by making SOPs for complementary therapy, especially in giving massage to pregnant women or pregnancy massage, which has been proven to be very helpful for pregnant women's discomfort during the second and third trimesters so that it helps mothers feel relaxed and comfortable.